Photochemical and Photocatalytic Deracemization Reactions - Hashemian, Seyed Parsa; Arabi Zanjani, Seyed Mohammad; Afshar Moghadam, Tara; Teimouri, Mohammad Bagher (SynOpen, 2024)
Under photochemical conditions using an appropriate chiral catalyst, racemic mixtures of compounds can be converted into enantioenriched mixtures through distinguished pathways known as photochemical and photocatalytic deracemization reactions. In this graphical review, we highlight photochemical deracemization reactions that proceed in the presence of light as the key element along with a suitable chiral photocatalyst.
Keywords: photochemical deracemization; chiral compounds; enantioenrichment; photocatalyst; photoredox